Knowledge society vs. knowledge economy : knowledge, power, and politics - Sörlin, Sverker; Vessuri, Hebe M. C. (Issues in higher education (New York, N.Y.), 2007)
A new collection in the IAU Issues in Higher Education Series that deals with the major tensions between education and science. Drawing on experiences from a range of countries and regions world-wide, the book demonstrates the need to find new avenues for the management of knowledge production to ensure that it can meet increasingly global goals and demands.